Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.clae.2020.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic: Important considerations for contact lens practitioners

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website.Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
113
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 93 publications
0
113
0
6
Order By: Relevance
“…The COVID-19 pandemic which has swept the world since the start of 2020 is unprecedented in modern times and is having a considerable impact on day-to-day lives including contact lens practice [1]. A recent review in this journal found no relationship between contact lens use and COVID-19 infection [2], perhaps in part because it is rare to find the SARS-CoV-2 virus even in the tear films of patients who have tested positive for the disease [3]. Similarly, bodies such as the United Kingdom College of Optometrists [4], the British Contact Lens Association [5] and the United States Centers for Disease Control and Prevention [6] have also indicated this same lack of association.…”
mentioning
confidence: 99%
“…The COVID-19 pandemic which has swept the world since the start of 2020 is unprecedented in modern times and is having a considerable impact on day-to-day lives including contact lens practice [1]. A recent review in this journal found no relationship between contact lens use and COVID-19 infection [2], perhaps in part because it is rare to find the SARS-CoV-2 virus even in the tear films of patients who have tested positive for the disease [3]. Similarly, bodies such as the United Kingdom College of Optometrists [4], the British Contact Lens Association [5] and the United States Centers for Disease Control and Prevention [6] have also indicated this same lack of association.…”
mentioning
confidence: 99%
“…The World Health Organisation (WHO) declared the rapid spread of cases of COVID-19 a pandemic on 11 th March, 2020. The COVID-19 pandemic is a challenging situation for the general population and especially for eye care practitioners working in close proximity to patients [1][2][3]. At the beginning of Austria and Switzerland were only offering emergency services during restricted opening times.…”
mentioning
confidence: 99%
“…However, eye protection is recommended not only for all health care workers, but also for various categories of people at risk (e.g., immunocompromised patients located in small rooms with poor ventilation, or older people living in close communities, such as health care residences) [27][28][29], and for individuals with ocular surface diseases (e.g., dry eye) or at risk of corneal ulcer (e.g., contact lens wearers). In this respect, personal eyeglasses and contact lenses do not qualify as personal protective equipment, although contact lenses remain a perfectly acceptable form of vision correction during the coronavirus pandemic, as long as people practice good hand hygiene and follow appropriate wear-and-care directions [20].…”
Section: Discussionmentioning
confidence: 99%